Synthesis of a biotinated amphiphile - Sabine, Amslinger; Hirsch, Andreas; Hampel, Frank (Tetrahedron, 2004)
The synthesis of a biotinated amphiphile assembled from d-(+)-biotin, ethylene diamine as spacer, galactaric acid and 1-dodecylamine was achieved in six steps. The key step was the synthesis of a bisacetonide protected galactaric ester, the structure of which was determined by X-ray analysis. Aminolysis, spacer attachment, coupling with biotin and deprotection led to the amphiphilic galactaramide. Graphical Abstract. © 2004 Published by Elsevier Ltd.